Character Education Curriculum of Primary School in Taiwan vs Indonesia: A Comparison Study: Teachers Implement Character Education - Efendi, Moch Yusuf; Maryono, Ahamd; Syarifah, Laili; Ha, Luong Ngoc (CV Sinergi Ilmu dan Publikasi, 2025)
This study employed a quantitative method with a comparative survey design to examine the character of education in primary school curricula in Taiwan and Indonesia. A total of 330 teachers (165 from each country) participated in the study. The research focused on curriculum content, character-building methods, and educational approaches. Data were collected through a structured questionnaire and analyzed using t-tests. The findings revealed that both countries emphasize character education through structured programs beyond formal learning. In Taiwan, the development program involves collaboration between principals and teachers, while in Indonesia, principals supervise teachers in implementing character values across intra- and extracurricular activities. This study used a quantitative survey design to compare character education in Taiwanese and Indonesian primary school curricula, involving 330 teachers from both countries. It examined curriculum content, character-building methods, and educational approaches in each system. Findings showed that both countries emphasize character education, with Taiwan favoring principal-teacher collaboration, while Indonesia emphasizes principal-led supervision in both intra- and extracurricular settings.